SPREADING INFORMATION - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
_ World Vision International, These, Senegal: ''I am grateful to Spore for publishing my article on the oil press. I have had more than 50 letters from NGOs, businesses, small-scale farmers and magazines from more than 15 countries in Africa,...